2011
DOI: 10.1111/j.1365-2648.2011.05811.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of nurse consultant roles in the United Kingdom: a mixed method systematic literature review

Abstract: kennedy f., mcdonnell a., gerrish k., howarth a., pollard c. & redman j. (2011) Evaluation of the impact of nurse consultant roles in the United Kingdom: a mixed method systematic literature review. Journal of Advanced Nursing 68(4), 721–742. Abstract Aim.  This paper reports a mixed methods systematic review examining the impact of nurse consultant roles in adult healthcare settings, with a view to identifying indicators for demonstrating their impact on patient and professional outcomes. Background.  Nurse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 42 publications
2
73
0
1
Order By: Relevance
“…Subsequent studies completed by Kennedy et al (2011) andGerrish et al (2013) have led to the development of an impact framework for consultant nurses through a comprehensive programme of work with in depth case studies. Three domains of impact have been identified -clinical, professional and organisational domains.…”
Section: Theoretical Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies completed by Kennedy et al (2011) andGerrish et al (2013) have led to the development of an impact framework for consultant nurses through a comprehensive programme of work with in depth case studies. Three domains of impact have been identified -clinical, professional and organisational domains.…”
Section: Theoretical Insightmentioning
confidence: 99%
“…Their findings suggest a largely positive influence of nurse consultants on a range of clinical and professional outcomes, which map onto the proposed impact framework. Kennedy et al's (2011) research is critical of the quality of the studies reviewed identifying very little robust evidence and methodologically weak quality. They propose further robust research is required to explore nurse consultants' impact on patient and professional outcomes and that their impact framework could be used to guide future research and assist nurse consultants assess their impact.…”
Section: Theoretical Insightmentioning
confidence: 99%
“…We then classified the systematic reviews according to the three types of mixed studies synthesis designs. The most common type of synthesis found in our sample was convergent (n = 8), of which seven were QUAL (4,13,16,42,45,46,87) and one QUAN (15). Three other mixed studies reviews were sequential, two of which used a sequential exploratory synthesis (67,76) and one used a sequential explanatory synthesis (12).…”
Section: Overview Of Mixed Studies Reviewsmentioning
confidence: 99%
“…Within Europe and the United States some evaluation of the impact of these roles on the profession, clinical care, education and the service user has been carried out by Bryant et al (2004), Begley et al (2010), Kennedy et al (2012) and Comiskey et al (2013) and all found positive impacts of the expanded role.…”
Section: Introductionmentioning
confidence: 99%
“…According to Riegel, Sullivan-Marx and Fairman (2012) nurse practitioners are nurses who have acquired advanced clinical and decision making skills and usually hold a master's degree. They assert that 23 countries formally recognise this role and believe these roles can be used to address some of the global demands within healthcare services and practice.Within Europe and the United States some evaluation of the impact of these roles on the profession, clinical care, education and the service user has been carried out by Bryant et al (2004), Begley et al (2010), Kennedy et al (2012) and Comiskey et al (2013) and all found positive impacts of the expanded role. …”
mentioning
confidence: 99%